Clinical Effectiveness of Viddha Karma in PCOS: A Case Report - Bhagyashree Jibkate; Akshay S. Pargaonkar; Mayuri Deshpande (Journal of Pharmacy and Bioallied Sciences)
Polycystic ovary syndrome (PCOS) is a common hormonal disorder affecting women of reproductive age. Ayurveda, an ancient Indian medical system, offers a comprehensive approach to addressing PCOS, including treatments like Viddha Karma. In the case of PCOS, Viddha Karma aims to relieve symptoms and enhance overall well-being. A 27 -year-old unmarried female patient came with complaints of irregular and scanty menses for the past 3-4 years, along with severe abdominal pain during the first 1-3 days of menstruation. She was treated with Shaman Chikitsa and Viddha Karma for 8 months. The patient’s menstrual cycle become regular, the volume of bleeding increased to a normal level, and she experienced a weight reduction of 5 kg. The examination of Viddha Karma principles in the management of PCOS emphasizes its potential as a supplementary treatment that tackles the underlying causes and promotes overall well-being. However, further research and clinical trials are necessary to gain a comprehensive understanding of its effectiveness.